Chastity in Vaduz - Peckenham, Juno (2002)
Museo de arte en Vaduz, Liechtenstein, por los arqs <Morger-Degelo-Kerez>
Keywords: MORGER, MEINRAD; DEGELO, HEINRICH; KEREZ, CHRISTIAN; MUSEOS; MUSEOS DE ARTE; VADUZ; LIECHTENSTEIN